2021
DOI: 10.3390/su13105493
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Olive Waste-Derived Biochar on Hydro-Physical Properties of Sandy Soil

Abstract: In this study, waste olive leaves and branches were pyrolyzed to produced biochar, and their impacts on physical and chemical properties of a sandy soil were evaluated. Pyrolytic temperatures of 300 °C, 400 °C, and 500 °C were used for biochar production. After evaluating the physio-chemical properties, the produced biochars were added to the top 10 cm layer of the soil at rates of 0%, 1%, 3%, and 5% in a column experiment at 25 °C. Biochar was mixed with a sandy soil into the top 10 cm of the columns. For all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…However, under these conditions, water in the root-zone would not be lost due to deep percolation and there should be more available water for plant growth. Similar results were reported earlier by various researchers [4,9,27,[36][37][38][39][40][41][42][43][44][45][46].…”
Section: Cumulative Infiltration and Infiltration Ratesupporting
confidence: 92%
“…However, under these conditions, water in the root-zone would not be lost due to deep percolation and there should be more available water for plant growth. Similar results were reported earlier by various researchers [4,9,27,[36][37][38][39][40][41][42][43][44][45][46].…”
Section: Cumulative Infiltration and Infiltration Ratesupporting
confidence: 92%
“…Ash content increased from 7.45 to 13.63%, and volatile matter decreased from 73.2% to 45.4% when the pyrolysis temperature increased from 300 to 600 °C. Many studies reported similar findings 4 , 9 , 35 , 38 .…”
Section: Resultsmentioning
confidence: 53%
“…These enhancements improve soil quality, increase water use efficiency, and reduce water stress on crop yields. Alghamdi et al 4 , 5 reported a significant decrease in soil-saturated hydraulic conductivity for all treatments compared to control after adding biochar produced at different pyrolysis temperatures and application rates.…”
Section: Introductionmentioning
confidence: 94%
“…Practices which could decrease the amount of irrigation water, without reducing yield, are required, especially in arid environments [3,5]. Therefore, the partial root zone drying (PRD) method, regulated deficit irrigation (RDI), and the addition of soil conditioners, such as biochar, are considered important approaches that can conserve irrigation water and increase yields and water productivity (WP) [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Limited research has compared and integrated the impact of RDI and PRD in the presence of biochar on irrigation water conservation and the effects on yield and water productivity (WP). Moreover, it is known that most of the groundwater used for irrigation in arid environment is saline; thus, there is definitely a need for investigating the effect of biochar application when using saline water for irrigation [7,14]. Consequently, the main objectives of this investigation were to; (1) investigate the impacts of RDI and PRD systems, and date-palm-derived biochar on water productivity (WP), the crop water response factor (Ky), and the final yield of tomato (Solanum lycopersicum) using fresh and saline water; (2) investigate the impact of PRD at different growth stages on tomato yield using two types of irrigation water, i.e., fresh and saline.…”
Section: Introductionmentioning
confidence: 99%